Testing English Grammar at PCL and Bachelor's Level - Yadav, Yogendra Prasad (Tribhuvan University Journal, 2010)
This paper aims to present an overview of the grammar component incorporated in the PCL and Bachelor's level courses for Compulsory English and to suggest items to test the component at the final examinations. The observations in the paper are largely based on Developing English Skills. English for Further Education and a Communicative Grammar of English. Key words: English Grammar; PCL; Grammar component Tribhuvan University Journal Volume XIV, 1991 Page: 9-14 Uploaded date: 5 October, 2010